2001
DOI: 10.1021/jp004396c
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Spectroscopy of N-Methylacetamide Revisited

Abstract: Although a lot of work has been performed on the vibrational analysis of N-methylacetamide (NMA), some uncertainties and even contradictions remain, mainly due to the fact that the structure of NMA at room temperature is not stable due to traces of water or due to the fact that the authors only studied the infrared or the Raman spectra. On the basis of the infrared and Raman spectra in the -196 °C to +100 °C temperature range, we have shown that the effects of temperature on the structure and the changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
124
0
15

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(145 citation statements)
references
References 84 publications
6
124
0
15
Order By: Relevance
“…Second, solid NMA shows an antiparallel,ˇ-sheet-like structure, for which it is known that the B g -type AI is at much higher wavenumbers than A g . 14 The 1600 cm 1 band invoked by Herrebout et al 59 appears at 1610 in the 10°C spectra of crystallized NMA and was assigned to a combination of modes at 992 and 628 cm 1 . 43 The situation is more complicated for the liquid phase.…”
Section: Delocalization Of Amide Vibrations In Oligo-/polypeptidesmentioning
confidence: 97%
See 1 more Smart Citation
“…Second, solid NMA shows an antiparallel,ˇ-sheet-like structure, for which it is known that the B g -type AI is at much higher wavenumbers than A g . 14 The 1600 cm 1 band invoked by Herrebout et al 59 appears at 1610 in the 10°C spectra of crystallized NMA and was assigned to a combination of modes at 992 and 628 cm 1 . 43 The situation is more complicated for the liquid phase.…”
Section: Delocalization Of Amide Vibrations In Oligo-/polypeptidesmentioning
confidence: 97%
“…Recently, Herrebout et al 59 reinvestigated the Raman and IR spectra of solid and liquid NMA at various temperatures. With respect to the solid state, they assigned the Raman band at 1656 cm 1 to a combination tone of unspecified fundamentals and a weak band at 1600 cm 1 (observed at 130°C) to the B 2g -type AI mode.…”
Section: Delocalization Of Amide Vibrations In Oligo-/polypeptidesmentioning
confidence: 99%
“…Two sharp peaks around 1400 cm -1 were assigned to the CCH 3 symmetric bend (1377 cm -1 ) and the NCH 3 symmetric bend (1416 cm -1 ) 23 which are not included in our calculation. Since the amide A mode is hidden underneath the broad O-H stretch band of water, different experimental values of solvent shift have been reported from Raman spectra (-184 cm -1 ) 57 and the infrared spectra of NMA in the D 2 O/HOD mixture (-78 cm -1 ). 27 Both S1 and S2 predict amide I peak shifts (-59 and -57 cm -1 ) and line widths (29 and 28 cm -1 ) in good agreement with experiment -80 cm -1 and 29 cm -1 .…”
Section: The Infrared Absorptionmentioning
confidence: 99%
“…As a characteristic amide band is often called amide I and has been the object of much attention, both in small amides [16] and in polymeric compounds [17,18]. In spite of this, a detailed interpretation of amide I spectra is still a matter of controversy [16].…”
Section: Infrared Spectra Of S-and (Rs)-atenolol In Solid Statementioning
confidence: 99%
“…Thus only 1671 and 1639 cm −1 are components of amide I. It has been observed that hydrogen bonding gives rise to a red shift of ν(C O) and a blue shift of δ(NH 2 ) [16]. A partial overlapping of the bands corresponding to these vibration modes thus occurs, making the spectra appear as a doublet [11].…”
Section: Infrared Spectra Of S-and (Rs)-atenolol In Solid Statementioning
confidence: 99%